2022
DOI: 10.3390/cancers14225651
|View full text |Cite
|
Sign up to set email alerts
|

[225Ac]Ac-SibuDAB for Targeted Alpha Therapy of Prostate Cancer: Preclinical Evaluation and Comparison with [225Ac]Ac-PSMA-617

Abstract: In the present study, SibuDAB, an albumin-binding PSMA ligand, was investigated in combination with actinium-225 and the data were compared with those of [225Ac]Ac-PSMA-617. In vitro, [225Ac]Ac-SibuDAB and [225Ac]Ac-PSMA-617 showed similar tumor cell uptake and PSMA-binding affinities as their 177Lu-labeled counterparts. The in vitro binding to serum albumin in mouse and human blood plasma, respectively, was 2.8-fold and 1.4-fold increased for [225Ac]Ac-SibuDAB as compared to [177Lu]Lu-SibuDAB. In vivo, this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…To this day FAPI α-therapy has only been reported in preclinical settings in mice with 225-Actinium ( 225 Ac-FAPI-04) [ 72 ]. 225 Ac is a pure α emitter that has seen application in prostate and neuroendocrine cancers [ 73 , 74 , 75 ]. This would require FAPI ligands with a long retention time in tumor lesions to make up for the long half-life of 225 Ac (9920 days) as well as 177 Lu (66,443 days).…”
Section: Discussionmentioning
confidence: 99%
“…To this day FAPI α-therapy has only been reported in preclinical settings in mice with 225-Actinium ( 225 Ac-FAPI-04) [ 72 ]. 225 Ac is a pure α emitter that has seen application in prostate and neuroendocrine cancers [ 73 , 74 , 75 ]. This would require FAPI ligands with a long retention time in tumor lesions to make up for the long half-life of 225 Ac (9920 days) as well as 177 Lu (66,443 days).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections (4 µm thickness) of paraffin-embedded spleen, kidneys and liver of mice from Study II were stained using hematoxylin and eosin and the histo(patho)logical analysis was performed by a board-certified veterinary pathologist (AnaPath Services GmbH, Liestal, Switzerland) using a pre- defined scoring system (Supplementary Material) [29].…”
Section: Methodsmentioning
confidence: 99%
“…A study by Meyer et al demonstrated that incorporating an extended linker with supplementary naphthyl groups enhances ligand binding to albumin, thereby extending circulating half-life 29 . Using a similar strategy, Busslinger et al developed ibuprofen containing ligand [ 225 Ac]Ac-SibuDAB, which showed similar radiolabeling and hematological effect as [ 225 Ac]Ac-PSMA-617, whereas the tumor uptake of the [ 225 Ac]Ac-SibuDAB doubled at 48 h as compared to [ 225 Ac]Ac-PSMA-617 (64 ± 11% IA/g vs. 31 ± 3% IA/g), resulting in improved therapeutic response and overall survival in animal models 30 . Another study with macropa chelator conjugated to albumin binding unit (4-(p-iodophenyl)butyrate) and one or two PSMA ligands also showed that the uptake of an albumin-bound [ 225 Ac]Ac-PSMA molecule was four times higher than the non-albumin binding counterpart 31 .…”
Section: Actinium-225 Based Tat Agents For Prostate Cancer Tumor Modelsmentioning
confidence: 99%